Surface passivation for silicon solar cells - Osorio, R (2015)
Passivation of silicon surfaces remains a critical factor in achieving high conversion efficiency in solar cells, particularly in future generations of rear contact cells –the best performing cell geometry to date. In this thesis, passivation is characterised as either intrinsic or extrinsic, depending on the origin of the chemical and field effect passivation components in dielectric layers. Extrinsic passivation, obtained after film deposition or growth, has been shown to improve significantly the passivation quality of dielectric films. Record passivation has been achieved leading to surface recombination velocities below 1.5 cm/s for 1 Ωcm n-type silicon covered with thermal oxide, and 0.15 cm/s in the same material covered with a thermal SiO2/PECVD SiNx double layer. Extrinsic field effect passivation, achieved by means of corona charge and/or ionic species, has been shown to decrease by 3 to 10 times the amount of carrier recombination at a silicon surface. A new parametrisation of interface charge, and electron and hole recombination velocities in a Shockley-Read-Hall extended formalism has been used to model accurately silicon surface recombination without the need to incorporate a term relating to space-charge or surface damage recombination. Such a term is unrealistic in the case of an oxide/silicon interface. A new method to produce extrinsic field effect passivation has been developed in which charge is introduced into dielectric films at high temperature and then permanently quenched in place by cooling to room temperature. This approach was investigated using charge due to one or more of the following species: ions produced by corona discharge, Na+, K+, Cs+, Mg2+ and Ca2+. It was implemented on both single SiO2 and double SiO2/SiNx dielectric layers which were then measured for periods of up to two years. The decay of the passivation was very slow and time constants of the order of 10,000 days were inferred for two systems: 1) corona-charge-embedded into oxide grown on textured FZ-Si, and 2) potassium ions driven into an oxide on planar FZ-Si. The extrinsic field effect passivation methods developed in this work allow more flexibility in the combined optimisation of the optical properties and the chemical passivation properties of dielectric films on semiconductors. Increases in cell Voc, Jsc and η parameters have been observed in simulations and obtained experimentally when extrinsic field effect passivation is applied to the front surface of silicon solar cells. The extrinsic passivation reported here thus represents a major advancement in controlled and stable passivation of silicon surfaces, and shows great potential as a scalable and cost effective passivation technology for solar cells.